Neuronal deletion of phosphatase and tensin homolog results in cerebellar motor learning dysfunction and alterations in intracellular signaling. Issue 8 (22nd May 2019) - Nolan, Suzanne O.; Jefferson, Taylor S.; Reynolds, Conner D.; Smith, Gregory D.; Holley, Andrew J.; Hodges, Samantha L.; Lugo, Joaquin N.
Abstract : The purpose of this investigation was to examine cerebellar levels of several molecular signaling pathways, including PI3K/AKT/mammalian target of rapamycin (mTOR) signaling and markers of neuronal migration, following loss of the phosphatase and tensin homolog ( PTEN ) gene in a subset of neurons, as well as the accompanying behavior phenotype in mice. Motor coordination and learning were measured by the sticker removal task and the accelerating rotarod. Western blots were conducted on cerebellar tissue samples. We demonstrated that neuron subset-specific deletion of PTEN in mice led to deficits in motor coordination. These changes were accompanied by alterations in many different proteins, including the PI3K/AKT/mTOR signaling pathway, FMRP, glutamate receptors, and neuronal migration markers. These data firstly support a role for hyperactivation of mTOR in the cerebellum following the loss of PTEN, accompanied by behavioral deficits. Moreover, the results of the current study support a broader role for PTEN signaling in early neuronal migration and organization of the cerebellum, and point to a putative role for PTEN in many neuropsychiatric conditions. Abstract : Supplemental Digital Content is available in the text.